2018
DOI: 10.1530/eje-18-0318
|View full text |Cite
|
Sign up to set email alerts
|

Active Cushing syndrome patients have increased ectopic fat deposition and bone marrow fat content compared to cured patients and healthy subjects: a pilot 1H-MRS study

Abstract: Accumulation of BMF is induced by hypercortisolism. In remission patients BMF reached values of controls. Further studies are needed to determine whether this increase in marrow adiposity in CS is associated with bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Our observation of no difference in BMA between CD and controls agrees with a previous study of adults with IBD in remission [55]. BMA has been reported to be increased at diagnosis of Cushing's disease [56,57], however it normalizes following treatment of the GC excess [57].…”
Section: Discussionsupporting
confidence: 93%
“…Our observation of no difference in BMA between CD and controls agrees with a previous study of adults with IBD in remission [55]. BMA has been reported to be increased at diagnosis of Cushing's disease [56,57], however it normalizes following treatment of the GC excess [57].…”
Section: Discussionsupporting
confidence: 93%
“…A recent work of Maurice and collaborators measured BMF content in CS patients by using MRS, which is considered the best available method for BMF quantification. They found that CS patients had increased BMF content compared to cured patients and healthy subjects (95). However further studies are required in order to clarify the precise link between BMF and bone microarchitecture in hypercortisolism.…”
Section: Hypercortisolismmentioning
confidence: 99%
“…37 On the other hand, accumulation of bone marrow fat returned to normal levels during remission. 36 These data suggest that long-term monitoring of body fat and metabolic factors is important after cure of Cushing's syndrome.…”
Section: Adipose Tissue After Cure Of Cushing's Syndromementioning
confidence: 93%
“…Patients with Cushing's syndrome also develop ectopic fat deposition. Increased epicardial and pericardial fat accumulation was observed without myocardial steatosis, whereas bone marrow also showed increased adiposity 36,37 …”
Section: Effects Of Gc Excess On Adipose Tissuementioning
confidence: 99%